Kontekstualisasi Teologi Keadilan Dalam Hukum Qisash Dan Poligami - Samsuddin Samsuddin (Al-Tafaqquh: Journal of Islamic Law, 2021)
This research is a discussion of "Contextualization of Justice in Qisash Law and Polygamy", Qishash is the giving of punishment to perpetrators of crimes that are commensurate with the actions committed against the victim. The application of the qishash law is a good step to take because the qishash law reflects a sense of justice, where people who commit acts get punished according to what they did. And polygamy is a marriage relationship that has more than one partner at the same time. The condition for doing polygamy in Islam is to be fair, so whoever is unable to act fairly then he is not allowed to do polygamy. This research uses a descriptive method, by describing the information in the relevant library materials. The data collection technique in this research is a documentary technique, namely, information is extracted through documents from various library materials, after which it is analyzed using content analysis, namely, examining the object of research through analysis of books, essays, magazines and articles as well as all forms of communication that can be analyzed.